Hypothenar hammer syndrome: A multicenter case–control study. Issue 11 (22nd August 2013) - Scharnbacher, Jutta; Claus, Matthias; Reichert, Jörg; Röhrl, Tobias; Hoffmann, Ulrich; Ulm, Kurt; Letzel, Stephan; Nowak, Dennis
Abstract Background The rarely diagnosed hypothenar hammer syndrome (HHS) is due to vascular damage to the distal part of the ulnar artery probably caused by acute or repetitive blunt trauma to the hypothenar region. To date, mainly case reports have been published, while epidemiological data are almost absent. Aim To identify potential risk factors for HHS. Method An interview‐based multicenter case–control study of 71 patients with HHS and 105 matched controls was conducted with standardized questions regarding disease specific variables, occupation, exposure of the hands to different types of trauma in occupational and leisure context. Medical data were verified from individual medical records. Results Multivariable logistic regression analysis revealed that using the hand as a hammer on a daily basis (adjusted odds ratio [aOR] 17.04, 95% CI 5.51–52.67) daily pressure to the palm of the hand (aOR 4.96, 95% CI 1.39–17.71), and daily exposure to vibrating tools (aOR 3.41, 95% CI 1.03–11.31) were significant risk factors for HHS. Conclusions This investigation represents one of the largest groups of patients with HHS described so far. Work‐related repeated blunt trauma to the palm of the hand significantly increases the risk of HHS. Am. J. Ind. Med. 56:1352–1358, 2013. © 2013 Wiley Periodicals, Inc.